Does "We" Matter for Esports Fans? Analyzing the Mediating Effects of the Sense of Fan Community on Team Identification and Fandom Behaviors - Kim Kibaek; Kim Minsoo; Han Jinwook; Kim Dongkyu; Lee Inyup (Sciendo, 2022)
As an emerging field of study, scholars have constantly compared esports and traditional sports to find similarities and differences between the two sports fields. As various studies have called for more studies regarding the fan communities of esports, the present study analyzed the mediating effect of the sense of the esports fan community between team identification and consumer behaviors. This study employed a path analysis technique, utilizing online survey responses from 182 participants who identified as fans of the esports team. The findings revealed that a sense of fan community did not have mediating effects by showing statistically non-significant (in)direct effects on consumer behaviors. In contrast, team identification showed a significant positive effect on the sense of fan community and some consumer behaviors. The implications of the study suggest that esports organizations should focus their marketing strategies on individual fan bases and strive to maintain the competitiveness of their leagues to attract more fans to esports.